Comprometimento organizacional e locus de controle em jovens trabalhadores: uma comparação entre participantes e não participantes de um programa social - Salgado, Alice Langoni (2008)
This study had as objectives to evaluate and to compare the affective, the normative and the calculative Organizational Commitment and locus of control orientation of young workers, being participants, former participants, and non-participants of a Training Program, as well as to verify the correlation between the locus of control orientation, demographic and professional data and Organizational Commitment in this sample. These objectives were defined based on the literature, where it could observe that the researches explore very few the relation between youngsters and work, and their professional education, even facing the Brazilian reality, with a growing amount of adolescents beginning early at the work market and, in this majority, with no professional qualities to face a strong competition. Therefore, a case study was developed in a great organization, of the contact center trade, from which were obtained three groups of employees: (G1) young trainers, (G2) ex young trainers, now employers, and (G3) employees never trained, fulfilling a sample of 190 participants, who answered previously validated scales of Locus of Control and Affective, Calculative and Normative Organizational Commitment. Not only were the scales developed, but also a questionnaire about personal and professional data. The whole instrument was applied in the institution where the first group participates of the Learning Program, as defined by the Federal Government and supported by the organization with the objective of professional qualification of youngsters. The second and the third groups answered the instruments in the organization, during off hours, in a spontaneous way, after having received information about the objectives of the study and agreed in participating. After the data collection, descriptive, correlation and variance analysis were performed using the SPSS Program. The results pointed that the groups which are or which were already trained had a mean significantly higher of Affective Commitment; men showed more normative commitment with the organization, more external (chance and powerful others) and less internal locus of control than women. The internal levels were high in the three groups and they were present in all analysis. In relation to the time of employment in that organization, significant differences were obtained in calculative and affective commitment, internal locus of control and chance locus of control. Concerning age, marital status and educational level, there were no significant differences among groups. Facing these results, the conclusion is that the hypothesis about differences between the three groups were partially confirmed, considering that differences in the Organizational Commitment and between the sub-groups by personal and professional variables were found. The fact that this is a case study limits the generalization of the results, even because the work in a contact center is more attractive to young people and women. Investigations with young workers with more heterogeneous characteristics, from different trades of business, can be suggested in order to clarify the variables related to organizational commitment for this particular group.